2022
DOI: 10.1155/2022/7923448
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Evolution Mechanism of Landslide with Retaining Wall Locked Segment

Abstract: The failure of locked segment-type slopes is often affected by rainfall, earthquake, and other external loads. Rainfall scours the slope and weakens the mechanical properties of rock-soil mass. At the same time, rainfall infiltrates into cracks of slope rock mass. Under the action of in situ stress, hydraulic fracturing leads to the development and expansion of rock cracks, which increases the risk of slope instability. Under seismic force, the slope will be subjected to large horizontal inertial force, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Wang et al 44 determined that the tangential angle of displacements–time curve before landslide instability was generally 89°–89.5° through statistical analysis, which was used as one of the early warning and prediction criteria of landslides. They proposed the displacement tangential angle criterion, and the value of tangential displacement angle was further determined through coordinate axis transformation 41 . The angle–time curve of a landslide is consistent with the displacement–time curve, and both have typical creep characteristics that can be divided into three stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al 44 determined that the tangential angle of displacements–time curve before landslide instability was generally 89°–89.5° through statistical analysis, which was used as one of the early warning and prediction criteria of landslides. They proposed the displacement tangential angle criterion, and the value of tangential displacement angle was further determined through coordinate axis transformation 41 . The angle–time curve of a landslide is consistent with the displacement–time curve, and both have typical creep characteristics that can be divided into three stages.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that the locked segment is of low brittleness 39 . Based upon the existing studies of locked-segment type landslides 40 , 41 , water, gypsum, and sand were selected to simulate the retaining-wall type locked segment with a mass ratio of 1:1.4:1. According to the same ratio of the cylindrical sample, using YAW6206 electro-hydraulic servo press to carry out a uniaxial compression test, the uniaxial compressive strength was 3.27 MPa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have pointed out that 20 any part that controls the stability of the slope can be defined as the ‘locked segment’, so the ‘locked segment’ is the key to analyzing the progressive failure of many slopes. Aiming at the locked landslide in the western region of Henan Province, China, Liu Handong et al 21 used a self-developed loading device to simulate external loads such as rainfall and earthquakes and carried out the evolution mechanism of the ‘retaining wall’ type locked segment landslide. Li Dongdong et al 22 carried out a series of large-scale landslide physical model tests using specific flume test equipment and tested the difference between the failure time and deformation behavior of the three locking section shapes under the same rainfall conditions.…”
Section: Introductionmentioning
confidence: 99%